Cycling stability and adsorption mechanism at room temperature of the upscaled Ni-doped hierarchical carbon scaffold. (15th May 2022) - Plerdsranoy, Praphatsorn; Poo-arporn, Yingyot; Chanlek, Narong; Kidkhunthod, Pinit; Kamonsutthipaijit, Nuntaporn; Suthirakun, Suwit; Fongkaew, Ittipon; Khajondetchairit, Patcharaporn; Pangon, Autchara; Utke, Rapee
Abstract: Hydrogen adsorption performance and mechanism upon cycling of the upscaled Ni-doped hierarchical carbon scaffold (HCS) are investigated. Upon 22 hydrogen ad/desorption cycles (T = 25–50 °C and p (H2 ) = 1–50 bar), the upscaled Ni-doped HCS shows excellent cycling stability with gravimetric capacity of up to 1.51 wt % H2 . This is due to mechanical stability of HCS and good distribution of Ni nanoparticles. Hydrogen adsorption mechanism of Ni-doped HCS upon cycling is experimentally and theoretically characterized. Besides dissociative adsorption onto the surface, hydrogen diffusion into the lattice structure of Ni is observed. The latter enhances with the number of ad/desorption cycles and alters the electron sharing mechanisms between Ni and H during adsorption. Highlights: First time upscaling Ni-doped hierarchical carbon scaffold (HCS) for storing H2 at room temperature. Excellent reversible capacity of 1.5 wt.% H2 upon 22 ad/desorption cycles. HCS with good mechanical stability and well-distributed Ni nanoparticles favoring cycling stability. First time proposing hydrogen adsorption mechanism upon cycling of Ni-doped HCS. Significant H diffusion into Ni lattice and deficient electron sharing of Ni with H upon cycling.